The combined effects of cardiometabolic index and high-sensitivity C-reactive protein on the risk of new onset stroke in a Chinese national prospective longitudinal cohort study - Fangfang Li; Yu He; Ali Yang; Mingrong Xia; Weizhou Zang; Jiewen Zhang (Lipids in Health and Disease)
Abstract Background The Cardiometabolic Index (CMI) represents a novel anthropometric measurement, which combines characteristics of adiposity and lipids. Since obesity, lipid metabolism, and inflammation may collectively facilitate the occurrence of stroke, we hypothesize that a combination of elevated levels of the CMI and high-sensitivity C-reactive protein (hs-CRP) increases the risk of future stroke among middle-aged and older Chinese adults. Methods This study included 8,973 participants aged 45 years or older from the China Longitudinal Study on Health and Retirement (CHARLS), who were stroke-free and underwent baseline evaluations between 2011 and 2012, with followed-up at 2013, 2015 and 2018. The exposures were CMI and hs-CRP, with CMI calculated using the formula [waist circumference (cm)/height (cm)] × [triglycerides (mmol/L)/HDL-C (mmol/L)]. The primary outcome was the occurrence of new-onset stroke events. Cox proportional hazards models and restricted cubic spline (RCS) analyses were conducted to examine the associations between CMI, hs-CRP, and their combined effects on stroke risk. Sensitivity analysis was further implemented to verify the robustness of the results. Results A total of 629 participants (7.01%) suffered new-onset stroke during follow-up. The risk for stroke increased with each elevating quartile of baseline CMI levels, with adjusted HRs and 95% CIs being 1.27 (0.98–1.66), 1.41 (1.08–1.83), and 1.46 (1.09–1.96) for Q2, Q3, and Q4, respectively. Moreover, participants with levels of hs-CRP ≥ 2 mg/L also had significantly higher stroke incidence compared to those with CRP levels < 2 mg/L (adjusted HR 1.24, 95% CI 1.05–1.47, p = 0.012). Specifically, those concurrently with the highest CMI quartile and levels of hs-CRP ≥ 2 mg/L had the highest risk of stroke (adjusted HR 1.90, 95% CI 1.32–2.74). The subsequent sensitivity analyses yielded consistent results, further corroborating the initial findings. Conclusions The combination of CMI and hs-CRP exhibited a significant association with stroke risk among middle-aged and older Chinese adults, highlighting the importance of joint assessments of these biomarkers for refining risk stratification and enhancing primary prevention strategies for stroke.